Bicycle helmet effectiveness is not overstated. (3rd October 2017) - Olivier, Jake; Radun, Igor
ABSTRACT: Objective : The objective of this study was to discuss the challenges in estimating bicycle helmet effectiveness from case–control studies of injured cyclists and to estimate helmet effectiveness from cases and available exposure data. Methods : Data were extracted from studies of cyclists in Seattle; Victoria and New South Wales, Australia; and The Netherlands. Estimates of helmet use were used as exposure to compute relative risks for Seattle and Victorian data. Cycling distance data are routinely collected in The Netherlands; however, these data cannot be disaggregated by helmet use, which makes it unsuitable for estimating helmet effectiveness. Alternative controls were identified from larger cohorts for the Seattle and New South Wales cases. Results : Estimates of helmet effectiveness were similar from odds ratios (ORs) using hospital controls or from relative risks (RRs) using helmet use estimates (Seattle: OR = 0.339, RR = 0.444; Victoria: OR = 0.500, RR = 0.353). Additionally, the odds ratios using hospital controls were similar when controls were taken from a larger cohort for head injury of any severity (Seattle: OR = 0.250, alt OR = 0.257; NSW: OR = 0.446, alt OR = 0.411) and for serious head injury (Seattle: OR = 0.135, alt OR = 0.139; NSW: OR = 0.335, alt OR = 0.308). Although relevant exposure data were unavailable for The Netherlands, the odds ratio for helmet effectiveness of those using racing, mountain, or hybrid bikes was similar to other estimates (OR = 0.371). Conclusions : Despite potential weaknesses with case–control study designs, the best available evidence suggests that helmet use is an effective measure of reducing cycling head injury.